UIGM Student Satisfaction Level with E-Learning Using End User Computing Satisfaction (Eucs) - Sahona, Amar; Sahona, M. Amaruna; M.Com, Terttiaavin's; Maja, Gergely (Scientechno: Journal of Science and Technology, 2023)
The Ministry of Education and Culture responded by issuing a policy of learning from home, through online learning, the current education system must be ready to make the leap to transform online learning for all students. E-learning is a distance learning process whose implementation is supported by computers and internet technology, so that the learning process can be carried out at any time without a meeting between lecturers and students. From the explanation above, a study was conducted that measured the Level of Satisfaction of E-learning Students at Indo Global Mandiri University using the End User Computing Sastification (EUCS) method. This research will analyze the level of student satisfaction using the E-learning web which has an important role in higher education. Analysis of the level of satisfaction using EUCS is expected to be a measuring tool for the success of a system The model of End User Computing Satisfication (EUSC) was developed by Doll & Torkzadeh. EUCS is a method that can be used to measure the level of satisfaction of users of a system, by comparing expectations and reality of a system. Evaluation using the EUCS model is more focused on end user satisfaction with technological aspects. The dimensions in End User Computing Satisfaction (EUCS) according to Doll & Torkzadeh are five, namely content (Content), accuracy (Accuracy), form (Format).From the results of data processing that has been done previously, it can be concluded in this study that the results of quantitative analysis on the variable respondents who strongly agree (SS) are 80.0%, who agree 20.0% so it can be concluded that user satisfaction with the performance of e-learning students of Indo Global Mandiri University, Faculty of Informatics Engineering is very satisfied.